A validity study to consult on a protocol of a home hazard management program for falls prevention among community dwelling stroke survivors - Ahmad Ainuddin, Husna; Romli, Muhammad Hibatullah; S. F. Salim, Mazatulfazura; Hamid, Tengku Aizan; Mackenzie, Lynette (Public Library of Science, 2023)
Objective: A fall after a stroke is common but the consequences can be devastating not only for the stroke survivors, but also for caregivers, healthcare, and the society. However, research on falls prevention among the stroke population are limited, particularly on home hazards assessment and home modifications, demanding for a study to be conducted. The aim of the study is to validate the protocol and content of a home hazard management program guided by the Person-Environment-Occupation (PEO) Model for falls prevention among community dwelling stroke survivors. Method: Researchers developed their own questionnaire for content validation which consist of 23 items that covers two domains, namely justification for telehealth home hazard management practice and the protocol’s overall methodology. Occupational therapists with at least one year of experience in conducting a home hazard assessment were consulted for the content validation of a two-group clinical controlled trial protocol utilizing a home hazard assessment, home modifications and education over the usual care. Written consent was obtained prior to the study. The occupational therapists were given a Google Form link to review the protocol and intervention based on the questionnaire and rated each item using a four-point Likert scale for relevance and feasibility. Open-ended feedback was also recorded on the google form. Content Validity Index (CVI), Modified Kappa Index and Cronbach’s Alpha was calculated for the content validity and reliability analysis. Results: A total of sixteen occupational therapists participated in the study. 43.7% of participants had a master’s degree, 93.7% worked in the government sector and 56.2% had six years and more experience on conducting home hazard assessments. Content validity of the protocol is satisfactory for relevancy and feasibility (CVI = 0.84, ranging from 0.5 to 1.00), and for the reliability (α = 0.94 (relevance) and α = 0.97 (feasibility), respectively. The Modified Kappa ranged from 0.38 to 1.00 for all items. Feedback was also received regarding the design and procedure of the study protocol which included participant’s selection criteria, sample size, equipment provided, cost, location, and care for the participants during the intervention. Conclusions: Introducing a home hazard management program to prevent falls among the stroke population is viewed relevant and feasible. Practical suggestions from the consultation panel were adopted, and minor adjustments were required to strengthen the protocol’s overall methodology. This study established a rigorous and robust experimental protocol for future undertaking.